Guidelines for an educational agreement policy in Spain - Manuel Fernández Cruz (Universidad de Granada, 2010)
The increase of the social concern for educative results with international comparison of the National Educational Systems performance has had an effect of the mediate diffusion of PISA reports among OCDE country members. In some of them, the poor global results obtained has shocked the public opinion that has started to look for political responsibilities of what is perceived as a progressive deterioration of the Educational System quality. This is what has happened in Spain where the publication of these reports has coincide with the diffusion of other comparative analysis of educational indicators among the 27 members of the European Union. Because of thisthere are voices strongly claiming for a large State Agreement on Educational Policy among the big parliamentary forces, social agents( unions and business men) and the different sectors of the educational community ( managers, teaching staff, families and students), to strengthen education and improve its results.